2004
DOI: 10.1093/glycob/cwh085
|View full text |Cite
|
Sign up to set email alerts
|

Brefeldin A and filipin distinguish two globotriaosyl ceramide/verotoxin-1 intracellular trafficking pathways involved in Vero cell cytotoxicity

Abstract: In verotoxin 1 (VT1)-sensitive cells, globotriaosyl ceramide (Gb3) bound VT1 is endocytosed and transported retrogradely to the Golgi/endoplasmic reticulum (ER). The importance of the Golgi-dependent retrograde transport of VT1 is now shown to vary as a function of both VT1 exposure time and concentration. Following 3 h exposure to < 50 ng/ml VT1, Vero cell cytotoxicity and protein synthesis inhibition is absolutely dependent on intact Golgi structure. However, after 24 h incubation with concentrations of VT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…A small fraction of VT1 that rapidly reaches the ER within 1 h (Johannes et al, 1997;Sandvig et al, 1992) would explain the low translocation at this time. VT1 accesses the ER within 3-6 h (Khine et al, 2004), and [ 125 I]VTA 1 translocation reached a maximum at this time. Since the detected VT1 subunits remained associated throughout retrograde transport from the Golgi to the ER (Fig.…”
Section: Cytosolic Translocation Of [ 125 I]vtamentioning
confidence: 99%
See 2 more Smart Citations
“…A small fraction of VT1 that rapidly reaches the ER within 1 h (Johannes et al, 1997;Sandvig et al, 1992) would explain the low translocation at this time. VT1 accesses the ER within 3-6 h (Khine et al, 2004), and [ 125 I]VTA 1 translocation reached a maximum at this time. Since the detected VT1 subunits remained associated throughout retrograde transport from the Golgi to the ER (Fig.…”
Section: Cytosolic Translocation Of [ 125 I]vtamentioning
confidence: 99%
“…BFA fuses the transGolgi network (TGN) and endosomes (LippincottSchwartz et al, 1991), and collapses Golgi and ER (Lippincott-Schwartz et al, 1989). BFA protects VT1-treated cells from apoptosis (Fujii et al, 2003) and protein synthesis inhibition (Donta et al, 1995;Khine et al, 2004). BFA presumably protects cells through its collapse of the Golgi, thereby preventing further retrograde transport to the ER, from which translocation is presumed to occur.…”
Section: Inhibition Of Retrograde Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…B subunit of Stx is supposed to be a convenient non-cytotoxic model ) of holotoxin internalization, and Stx A subunit lacks known trafficking motifs (Jackson et al 1999); the A subunit might also modify holotoxin transport via unknown motifs. Nevertheless, it has been known that holotoxin initial internalization will be A subunit-independent, and two pathways have been identified as applicable to holotoxin endocytosis (Khine et al 2004). Moreover, two distinct Gb3/ CD77 signaling pathways leading to apoptosis have been triggered by Anti-Gb3/CD77 mAb and Stx (Tétaud et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different intracellular routing may play a pivotal role in cell susceptibility and triggering a different pathway for apoptosis. Stxinduced apoptosis and cytotoxicity are distinct processes (Gordon et al 2000;Williams et al 1999), although the A subunit can be necessary for apoptosis (Khine et al 2004). In our study, the same result was also shown, as if A subunit can separately induce apoptosis morphologically in higher concentration by Hoechst staining and DNA laddering method.…”
Section: Discussionmentioning
confidence: 99%